Monetary theory and policy in Africa (symposium papers) : January 21-24, 1980, Dakar, Senegal - Association of African Central Banks; African Centre for Monetary Studies (Dakar, Senegal : African Center for Monetary Studies, 1981)
The book is a collection of papers presented at the symposiums organized by Association of African Central Banks from January 21 - 24, 1980 in Dakar Senegal which center on Monetary theory and policy in Africa.
Includes bibliographical references.
usc 18/10/18
Loans
Keywords: Monetary policy; Banks and banking